2022
DOI: 10.3389/fonc.2022.841418
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Relapses Show Increased Markers of Vulnerability to Ferroptosis

Abstract: BackgroundDespite the availability of various therapy options and being a widely focused research area, the prognosis of glioblastoma (GBM) still remains very poor due to therapy resistance, genetic heterogeneity and a diffuse infiltration pattern. The recently described non-apoptotic form of cell death ferroptosis may, however, offer novel opportunities for targeted therapies. Hence, the aim of this study was to investigate the potential role of ferroptosis in GBM, including the impact of treatment on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The chemical inhibition, stable silencing, or depletion of ACSL4 demonstrated it can diminish necrosis and aggressiveness of glioblastoma (Yee et al, 2020). However, in the recurrent glioma, the expression of ACSL4 was found significantly increased, indicating glioblastoma relapses may be higher vulnerable to ferroptosis (Kram et al, 2022). Catalyzes the conversion of long-chain FA to acyl-CoAs for both synthesis of cellular lipids Preferred substrates: oleic acid and linoleic acid (Kanter et al, 2012) Glioma (Wang et al, 2018;Zhou et al, 2019;Xu et al, 2022) Amyotrophic lateral sclerosis (ALS) (Ben-Zaken et al, 2022) ACSL3…”
Section: Gliomamentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical inhibition, stable silencing, or depletion of ACSL4 demonstrated it can diminish necrosis and aggressiveness of glioblastoma (Yee et al, 2020). However, in the recurrent glioma, the expression of ACSL4 was found significantly increased, indicating glioblastoma relapses may be higher vulnerable to ferroptosis (Kram et al, 2022). Catalyzes the conversion of long-chain FA to acyl-CoAs for both synthesis of cellular lipids Preferred substrates: oleic acid and linoleic acid (Kanter et al, 2012) Glioma (Wang et al, 2018;Zhou et al, 2019;Xu et al, 2022) Amyotrophic lateral sclerosis (ALS) (Ben-Zaken et al, 2022) ACSL3…”
Section: Gliomamentioning
confidence: 99%
“…Modulates prostaglandin E2 secretion. Preferred substrates: arachidonate (Klett et al, 2017) Central nervous system Glioma (Zhou et al, 2019;Cheng et al, 2020;Tan et al, 2020;Yee et al, 2020;Yi et al, 2020;Dattilo et al, 2021;Hacioglu and Kar, 2022;Kram et al, 2022;Miao et al, 2022) Cerebrovascular diseases: ischemic stroke (Gubern et al, 2013;Li et al, 2019;Chen J. et al, 2021;Cui et al, 2021;Guo H. et al, 2021;Li C. et al, 2021;Liao et al, 2021;Tuo et al, 2022), hemorrhage (Chen B. et al, 2021;Jin et al, 2021), subarachnoid hemorrhage (Qu et al, 2021;Huang et al, 2022;Yuan et al, 2022) Injury: traumatic brain injury (Kenny et al, 2019;Xiao et al, 2019;Bao Z. et al, 2021), spinal cord injury (Zhou et al, 2020;Pang et al, 2022) Intellectual disability: non-syndromic X-Linked intellectual developmental disorder (Meloni et al, 2009;Zhang et al, 2009;Liu et al, 2011Liu et al, , 2014Huang et al, 2016;Chang et al, 2019;Jia et al, 2019), Alport syndrome with intellectual disability (Rodriguez et al, 2010;Smetana et al, 2021) Neurodegenerative diseases: Alzheimer's disease (AD) (Rapoport, 2008;…”
Section: Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…FSP1 works as an oxidoreductase reducing ubiquinone (Coenzyme Q10) to its antioxidant form ubiquinol (CoQH2), which acts as a lipophilic radical scavenger that limits the lipid peroxide accumulation in the absence of GPX4, or complementary to GPX4 activity [75]. Interestingly, pharmacological inhibitors of FSP1 such as iFSP1 synergizes with GPX4 modulation to trigger ferroptosis in FSP1 overexpressed cells [76,77], and iFSP1 can sensitize several cancer cells to ferroptosis [78]. Similarly, dihydroorotate dehydrogenase (DHODH) has also demonstrated an anti-ferroptotic role by regulating ubiquinol activity, inhibiting lipid peroxidation and suppressing ferroptosis induction [79].…”
Section: The Gpx4 Pathwaymentioning
confidence: 99%
“…Conversely, activation of the p38 and ERK pathways in GBM decreased the levels of GPX4 protein (76). Helena Kram et al (77) performed immunohistochemistry on sample pairs of primary and relapse GBM of 24 patients who had received standard adjuvant treatment with radiochemotherapy. They found that the expression of GPX4 decreased significantly during tumor relapse.…”
Section: Gpx4mentioning
confidence: 99%